Baicalin and baicalein against myocardial ischemia-reperfusion injury: A review of the current documents - Nasiri, Reza; Arefnezhad, Reza; Baniasad, Kimia; Hosseini, Seyed Ali; Jeshari, Ahmadreza Samandari; Miri, Mostafa; Sahebkar, Amirhossein (Churchill Livingstone, 2025)
Myocardial ischemia-reperfusion injury (MIRI) is a significant challenge in the treatment of ischemic heart disease (IHD), arising as a complication from reperfusion therapies designed to restore blood flow after an ischemic event. Despite the availability of various therapeutic strategies, finding an effective treatment for MIRI remains difficult. Baicalin and its aglycone form (baicalein), natural compounds derived from the Chinese skullcap plant (Scutellaria baicalensis), have shown promise due to their antioxidant, anti-inflammatory, and cardioprotective properties. This review aims to explore the potential of baicalin and baicalein as treatments for MIRI, with a focus on their molecular and cellular level effects. These natural agents can decrease oxidative stress by promoting antioxidant enzymes and decreasing harmful oxidative substances that damage cardiac cells. They also exert anti-inflammatory effects by blocking specific pathways that trigger the release of inflammatory mediators. Additionally, they also improve heart cell survival, infarct region, and overall cardiac function by inhibiting key signaling pathways involved in cell death. Research in both animal and cell models suggests that these flavonoids, especially baicalin, can restore cardiac health following MIRI, improving cardiac performance, and reducing cardiac damage. These findings underscore the potential of baicalin and baicalein as therapeutic options for MIRI. However, further research and clinical trials are necessary to elucidate their mechanisms fully and to develop baicalin into a viable treatment.
Keywords: Myocardial ischemia-reperfusion injury; Pathogenesis; Baicalin; Baicalein; Treatment